The Athlete Biological Passport: an integral element of innovative strategies in antidoping - Vernec, A. R. (British Journal of Sports Medicine, 2014)
Concern for the health of athletes and integrity of sport resulted in the banning of specific substances although many years passed before analytical testing took place. Soon doping control programmes became synonymous with urine tests and adverse analytical findings. This system has its limits due to the detection window of prohibited substances, the timing of sample collections and the sophistication of some doping regimens. There have been a number of situations where these limits were demonstrated by athletes who proclaimed innocence based on passing their analytical tests only to later confess to doping. New strategies were called for to protect clean athletes. In the current World Anti-Doping Code, there are eight means to an Anti-Doping Rule Violation (ADRV). Article 2.2 states that the use of a prohibited substance may be established by any reliable means including witness statements, documentary evidence or evaluations of longitudinal profiling. In 2006, the World Anti-Doping Agency (WADA) with the support of some International Federations (IFs) gathered a group of experts to develop a harmonised programme on longitudinal profiling, or serial analysis of indirect biomarkers of doping, that was both scientifically and legally robust. This culminated in the WADA Athlete Biological Passport (ABP) Operating Guidelines and Technical Documents, published in 2009. The ABP is a paradigm that infers the use of prohibited substance (or method) by the monitoring of discriminant biomarkers over time. The haematological module detects blood manipulation by the use of erythropoietic stimulating agents or via blood transfusions. The steroidal module aims to identify endogenous anabolic androgenic steroids when administered exogenously and other indirect steroid doping substances or methods. Other ABP modules (endocrine, `omics`) are being developed. The term passport, first coined in 2000, is now defined in the ABP Guidelines as the longitudinal profile and all other relevant information including training, competitions and information derived from investigations. In the 2015 World Anti-Doping Code, investigations or enquiries gathered from other sources will play an even more prominent role.